Development and application of computational tools to analyse selectivity in organic chemistry - Jackson, K (2016)
The work described in this thesis illustrates how a range of computational methods may be applied to explain, both experimentally observed and computationally predicted, selectivity, in the field of Organic Chemistry. We begin with a discussion of the theory behind Computational Chemistry and also background to the ever growing field of organocatalysis, followed by a synopsis on the importance of asymmetry in synthesis. The second chapter focusses on an asymmetric organocatalysed reaction for the diastereoselective and enantioselective synthesis of the morphan motif. We look at a range of primary amine organocatalysts in this section, and are able to account for the observed asymmetry that is imparted, both qualitatively and quantitatively. Furthermore, through the course of our investigation, we were able to propose synthetic modifications to an existing organocatalyst used in this reaction, resulting in improvement to the enantioselectivity and atom economy of the reaction. In chapter three, we examine the various factors influencing ring closing reactions for a range of systems and investigate the origin of the underlying preference for cyclisations to follow Baldwin’s rules for selectivity. In order to do this, we use a range of computational techniques, including nucleus independent chemical shift (NICS) analysis to gain a better understanding of the magnetic properties of ring closing transitions structures (TS). Chapter four contains an in depth look into the stereoelectronic effects altering enantioselectivity in alkylation reactions with bicyclic enamine chiral auxiliaries. In this study, we were able to develop, improve, and implement a new methodology for explaining stereoselective alkylations of tropane-type enamine systems. Our computationally derived predictions of selectivity made for a number of systems have been subsequently verified with experimental results which were within 5 kJ/mol of our values. In chapter five, we use computational analysis to provide insight into the regiodi-vergent α- and α’-lithiation-electrophile trapping of N-thiopivaloyl- and N-(tert- butoxythiocarbonyl)-α-alkylazetidines. We calculated the magnitudes of rotational barriers for a range of protected azetidine systems and showed that rotamer interconversion could not occur for the aforementioned species at the temperature and on the time scale of the lithiations. In the final chapter, we describe the development of computational tools that have been essential in the other investigations discussed in this thesis. We also look at potential future applications of these programs in the field of Organic Chemistry.